Strategi Pengelolaan Keamanan dan Keselamatan dalam Penyelenggaraan Haji dan Umroh - Rayhan, Muhammad; Dimas Tri Frasetiyo; Muhammad Mu’tasim Billah; Abdul Hafiz (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Security and safety management strategies in organizing the Hajj and Umrah. The introduction explains the importance of a comprehensive strategy to minimize risks and ensure that religious services run smoothly. The theoretical study highlights the concept of the Welfare State and Law Number 13 of 2008 as the legal basis. The results and discussion show the need for risk management, congregation protection, and collaboration with related parties. The conclusion emphasizes the importance of integrated strategies in organizing the Hajj and Umrah pilgrimages.